Factors Affecting Income of Pineapple Small Farmers: Case Study at Tangkit Baru Village, Jambi Province, Indonesia - kaido, boris (Advances in Social Sciences Research Journal, 2020)
This study was conducted in Tangkit baru village, Jambi Province, Indonesia. The Study area was selected purposively based on this village which has produced the highest pineapple conducted by small farmers in Jambi Province. This study aims to determine the factors that affect the income of a small farmer pineapple in Tangkit baru village. The study aims were analyzed in descriptive methods and multiple linear regression analysis. The number of respondents was taken in the Slovin method, with 42 respondents. Data collection used the interview method with the questionnaire conducted directly in the study area. The data were analyzed quantitatively, the results study showed that all variables affected the farmer’s income, it was seen as a significance value of 0.000 < α 5%. Partially, the variables that affect the farmer’s income are field scale (X7) and labor factor (X6), while the variables that have no significant effect on pineapple small farmer’s income are the land rent (X4) and fertilizer (X1).